Effects of discontinuation of levothyroxine treatment in older adults: protocol for a self-controlled trial - Ravensberg, A Janneke; Poortvliet, Rosalinde K E; Du Puy, Robert S; Dekkers, Olaf M; Mooijaart, Simon P; Gussekloo, Jacobijn (BMJ open, 2023)
BackgroundMany older persons use the thyroid hormone levothyroxine which is often continued for life. Scientifically, there is much uncertainty whether simple continuation is the optimal approach. First, the physical need for levothyroxine can decrease with age thereby posing a higher risk of overtreatment and adverse effects. Second, large trials in subclinical hypothyroidism have shown no benefit for the use of levothyroxine. Interestingly, guidelines do not address re-evaluation of the indication. This self-controlled trial aims to determine the effects of discontinuation of levothyroxine treatment in older adults.Methods and analysisParticipants are community-dwelling subjects aged ≥60 years using levothyroxine continuously at a stable dosage of ≤150 µg and a level of thyroid-stimulating hormone (TSH) <10 mU/L. After a control period of 12 weeks, levothyroxine treatment is discontinued gradually using a stepwise approach with regular monitoring of thyroid function guided by their GP. The primary outcome is the proportion of participants withdrawn from levothyroxine while maintaining a free T4 level within the reference range and a TSH level <10 mU/L, 52 weeks after the start of discontinuation. Secondary outcomes are compared with the control period (self-controlled) and include among others, the effects on thyroid-specific and general health-related quality of life. Furthermore, patients’ attitudes towards deprescribing and regret regarding discontinuing levothyroxine treatment will be recorded. A total of 513 participants will be recruited to estimate the expected proportion of 50% with a 95% CI ranging from 45% to 55%.Ethics and disseminationApproval was obtained from the institutional Medical Ethics Committee. The Older People Advisory Board Health and Well-being has reviewed the research proposal and their comments were used for improvement. In line with the funding policies of the grant organisation funding this study, the study results will be proactively disseminated to the general public and key public health stakeholders.Trial registration numberNL7978; NCT05821881.